2023
DOI: 10.34190/ecsm.10.1.1055
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Motivations for SMEs in South Africa to Adopt Social Media

Abstract: Since the covid-19 pandemic in 2020, many businesses have relied on social media to stay abreast with the latest news, developments and to predict the future world of business. Many countries around the world instigated lockdown restrictions to curb the spread of the covid-19 virus, and social media platforms were very popular tools used for spreading the news. The proliferation of social media has also increasingly drawn the attention of Small and Medium Enterprises (SMEs) in South Africa to improve their eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Moreover, it offers a great opportunity to spread customers' positive e-word-of-mouth in their social connections, which is the primary reference source for online buyers (Shi and Chow, 2015). Previous studies have shown keen interest in exploring the various aspects of online platform adoption by SMEs, JEIM 37,3 including the impact of environmental, organizational and managerial factors (Wamba and Carter, 2016); ways to improve consumer engagement (Cheng and Shiu, 2019); using social media for knowledge management (Mamorobela and Buckley, 2018); and selecting a strategic location for e-commerce adoption (Awa et al, 2015). However, other research gaps in the literature on s-commerce adoption need researchers' attention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it offers a great opportunity to spread customers' positive e-word-of-mouth in their social connections, which is the primary reference source for online buyers (Shi and Chow, 2015). Previous studies have shown keen interest in exploring the various aspects of online platform adoption by SMEs, JEIM 37,3 including the impact of environmental, organizational and managerial factors (Wamba and Carter, 2016); ways to improve consumer engagement (Cheng and Shiu, 2019); using social media for knowledge management (Mamorobela and Buckley, 2018); and selecting a strategic location for e-commerce adoption (Awa et al, 2015). However, other research gaps in the literature on s-commerce adoption need researchers' attention.…”
Section: Introductionmentioning
confidence: 99%